Calibration model of polarimeters on board the Aerosol-UA space mission. (May 2019) - Milinevsky, Gennadi; Oberemok, Yevgen; Syniavskyi, Ivan; Bovchaliuk, Andrii; Kolomiets, Ivan; Fesianov, Ihor; Wang, Yuke
Highlights: Calibration procedure for Aerosol-UA space mission polarimeters has been developed. Expected polarimetric accuracy of the scanning polarimeter is ≤0.1%. Multispectral imager-polarimeter will provide polarimetric accuracy ≤1%. Measurement accuracy will allow to study the atmospheric aerosol microphysics. Abstract: The polarimetric model has been developed for calibration of the multispectral Scanning Polarimeter (ScanPol) and the MultiSpectral Imaging Polarimeter (MSIP) of the Aerosol-UA space mission. ScanPol and MSIP polarimeters are designed to provide high precision measurements of the atmospheric/earth surface radiation polarization with a substantial cross-track spatial coverage. The main sources of the instrumental errors, such as the finite extinction ratios of polarizers and the phase retards of telescopes are simulated in the polarimetric model. The mirrors mismatching, dark reference signal, the difference in the polarimeter channels gain, and the instrumental depolarization factor are modeled as additive values and scalar multipliers. The polarimetric model is derived in the form of Mueller matrices, which describe the transformation from the incoming polarized radiation to the measured signal. The parameters of the model are estimated experimentally. The numerical experiments have been carried out to validate the effectiveness of the proposed calibration procedures. The results have shown the possibility to minimize the ScanPol polarization errors below 0.15% (DoLP) and 0.2° (AoLP), and the MSIP polarization errors below 1%. The set of two polarimeters, namely the along-track scanner and the wide-angle imager, allows providing the in-orbit cross-calibration of the MSIP using the ScanPol measurements when their fields of view are overlapped. The concept of the MSIP and ScanPol polarimeters cross-calibration is discussed in the paper.